2017
DOI: 10.3126/jsan.v4i1.17384
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of ultrasound-guided abdominal nerve blocks and subarachnoid block as an anaesthetic technique for appendectomy: a retrospective study

Abstract: Background: Ultrasound guided abdominal nerve blocks are increasingly being used for anaesthesia and analgesia for surgeries like appendectomy, hernia repair in our centre. The aim of the study was to compare abdominal nerve blocks and subarachnoid block for appendectomy.Method: Retrospective data of patients that underwent appendectomy either under subarachnoid block (Group-S) or abdominal nerve blocks (Group-A) for three months were collected from hospital records. The groups were compared for conversion to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
1

Year Published

2018
2018
2019
2019

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 9 publications
0
1
1
Order By: Relevance
“…This finding indicates length of hospital stay is varying for different types of surgical procedures. Duration of hospital stay for appendectomy in this study is slightly higher than the other studies conducted in Nepal which showed mean hospital stay ranges from 3.19 (2.16) days to 5.14 (0.72)days [5,10]. It ranges from 5.15(0.09) days to 4.76 (0.01) days in Taiwan [11,12] and 4.1(0.8) days in India [13].…”
Section: Discussioncontrasting
confidence: 59%
“…This finding indicates length of hospital stay is varying for different types of surgical procedures. Duration of hospital stay for appendectomy in this study is slightly higher than the other studies conducted in Nepal which showed mean hospital stay ranges from 3.19 (2.16) days to 5.14 (0.72)days [5,10]. It ranges from 5.15(0.09) days to 4.76 (0.01) days in Taiwan [11,12] and 4.1(0.8) days in India [13].…”
Section: Discussioncontrasting
confidence: 59%
“…However, in the developing countries, the perioperative use of ultrasound has, until now, been limited to USG-guided regional anesthesia [ 3 ] and vascular access [ 4 ]. There are reports of its use in other perioperative settings [ 5 ].…”
Section: Discussionmentioning
confidence: 99%